Pengaruh Work-Life Balance terhadap Psychological Wellbeing - Nazwa Adelya Suhardi; Djamhoer, Temi Damayanti (Bandung Conference Series: Psychology Science, 2024)
Abstract. Factory employees often face their own difficulties in achieving a balance between the demands of work and personal life, which can have a significant impact on their psychological well-being. The purpose of this study is to see how high work-life balance and psychological wellbeing are, as well as to see the effect of work-life balance on psychological wellbeing. The research uses quantitative methods that are non-experimental causality, analysis using simple linear regression. The population in this study were employees of Production Plant 1A and 1B PT Pupuk Kujang, with stratified random sampling technique obtained 68 samples. The measuring instrument used in this study is the work-life balance scale from Fisher (2002) which has been adapted by Gunawan et al., (2019) and the psychological wellbeing scale from Ryff (1989), which has been adapted to Indonesian culture and language by Rachmayani & Ramdhani (2014). The results of the analysis state that there is an effect of work-life balance on psychological wellbeing with a significance value of p=0.000, the effect of work-life balance variables on psychological wellbeing variables is 27% and the regression coefficient result is -1.326 which means the effect is opposite. In addition, the results of the analysis also stated that 50% of respondents had high work-life balance and 51% of respondents had low psychological wellbeing. Abstrak. Karyawan pabrik sering menghadapi kesulitan tersendiri dalam mencapai keseimbangan antara tuntutan pekerjaan dan kehidupan pribadi, yang dapat berdampak signifikan pada kesejahteraan psikologis mereka. Tujuan penelitian ini adalah untuk melihat seberapa tinggi work-life balance dan psychological wellbeing, juga melihat pengaruh work-life balance terhadap psychological wellbeing. Penelitian menggunakan metode kuantitatif yang bersifat kausalitas non experimental, analisis menggunakan regresi linear sederhana. Populasi pada penelitian ini adalah karyawan Pabrik Produksi 1A dan 1B PT Pupuk Kujang, dengan teknik pengambilan sampel stratified random sampling diperoleh 68 sampel. Alat ukur yang digunakan dalam penelitian ini adalah skala work-life balance dari Fisher (2002) yang sudah diadaptasi oleh Gunawan et al., (2019) dan skala psychological wellbeing dari Ryff (1989), yang sudah diadaptasi ke budaya dan bahasa Indonesia oleh Rachmayani & Ramdhani (2014). Hasil dari analisis menyatakan bahwa terdapat pengaruh work-life balance terhadap psychological wellbeing dengan nilai signifikansi p=0.000, pengaruh variabel work-life balance terhadap variabel psychological wellbeing sebesar 27% dan hasil koefisien regresi sebesar -1,326 yang berarti pengaruhnya berlawanan. Selain itu, hasil analisis juga menyatakan bahwa 50% responden memiliki work-life balance tinggi dan 51% responden memiliki psychological wellbeing rendah.